1995
DOI: 10.1016/0014-5793(95)00598-4
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of 14‐3‐3 protein can form homo‐ and heterodimers in vivo and in vitro: implications for function as adapter proteins

Abstract: 14-3-3 proteins play a role in many cellular functions: they bind to and regulate several proteins which are critical for cell proliferation and differentiation. 14-3-3 proteins exist as dimers, and in this study we have shown that diverse 14-3-3 proteins can form both homo-and heterodimers in vitro (by crosslinking studies) and in vivo (by coimmunoprecipitation and Western blot analysis); this interaction is mediated solely through the N-terminal domain of the proteins. The composition of 14-3-3 dimers within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(213 citation statements)
references
References 19 publications
4
201
1
7
Order By: Relevance
“…Of note, we observed insolubilization of several 14‐3‐3 isoforms while S232 phosphorylation is specific to 14‐3‐3 θ . As 14‐3‐3 θ can heterodimerize with other isoforms38, 39, 40, these findings suggest that increased S232 phosphorylation of 14‐3‐3 θ may be sufficient to drive insolubilization of other isoforms through heterodimerization.…”
Section: Discussionmentioning
confidence: 89%
“…Of note, we observed insolubilization of several 14‐3‐3 isoforms while S232 phosphorylation is specific to 14‐3‐3 θ . As 14‐3‐3 θ can heterodimerize with other isoforms38, 39, 40, these findings suggest that increased S232 phosphorylation of 14‐3‐3 θ may be sufficient to drive insolubilization of other isoforms through heterodimerization.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that, apart from , several of the isoforms are able to form heterodimers (2,3). The presence of unique residues at the dimer interface provided a clear structural explanation for its homodimerization preference (38).…”
Section: Resultsmentioning
confidence: 96%
“…The identification of coisolated proteins by mass spectrometry revealed interaction of Pik1p, Bmh1p/Bmh2p, and Frq1p ( Figure 1E), whereas other proteins represented common contaminants of the TAP procedure (Shevchenko et al, 2002). We conclude that the Pik1p-14-3-3 complex occurs in vivo and includes both Bmh1p and Bmh2p, which often function as a heterodimer (Jones et al, 1995).…”
Section: Pik1p Binds To the 14-3-3 Proteins Bmh1p And Bmh2pmentioning
confidence: 82%